2010
DOI: 10.1051/0004-6361/200913306
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties and robustness of the ignition process in type Ia supernovae

Abstract: Context. It is widely accepted that the onset of the explosive carbon burning in the core of a carbon-oxygen white dwarf (CO WD) triggers the ignition of a type Ia supernova (SN Ia). The features of the ignition are among the few free parameters of the SN Ia explosion theory. Aims. We explore the role for the ignition process of two different issues: firstly, the ignition is studied in WD models coming from different accretion histories. Secondly, we estimate how a different reaction rate for C-burning can aff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…With such a resonance, even of moderate strength, bubbles run away closer to the center than predicted by using the CF88 rate (see also Iapichino & Lesaffre 2010). On the other hand, if the resonance were strong enough to provoke an offcenter ignition, it would have the opposite effect.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…With such a resonance, even of moderate strength, bubbles run away closer to the center than predicted by using the CF88 rate (see also Iapichino & Lesaffre 2010). On the other hand, if the resonance were strong enough to provoke an offcenter ignition, it would have the opposite effect.…”
Section: Discussionmentioning
confidence: 89%
“…Cooper et al (2009) studied the changes induced by such a resonance on the physics of superburst ignition on accreting neutron star crusts. Bennett et al (2010a) and Bennett et al (2010b) explored the impact on the s-process induced by an increase in the carbon fusion reaction rate up to a factor 50 000 at T = 5 × 10 8 K. Finally, Iapichino & Lesaffre (2010) analyzed the influence of uncertainties in the 12 C + 12 C reaction at T 5 × 10 8 K on the ignition of the WD core. They found that the ignition density depends slightly on the presence of a low-energy resonance while the ignition temperature is almost unaffected.…”
Section: Introductionmentioning
confidence: 99%
“…We also note recent considerations of the role of a possible 1 2C+ 1 2C resonance on the ignition of a type 1a supernovae [15] [16]. Though screening issues were not addressed in either of these works, the plasma coupling is strong enough in this application that they need to be.…”
Section: Discussionmentioning
confidence: 99%
“…These efforts have been accompanied by new developments in the physics of the explosion which have shown that even if pure deflagration models can reproduce many SN Ia spectra and light curves , in some cases a delayed detonation may be necessary (Khokhlov 1991;Röpke et al 2007). The physics of both the transition to detonation and ignition of the deflagration wave remains uncertain (Iapichino et al 2006;Röpke 2007;Iapichino & Lesaffre 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We foresee the application of these simplified networks or their modification in detailed one or multi-dimensional stellar evolution models trying to understand presupernova CO WDs or similar objects (see, e.g., Lesaffre et al 2006;Zingale et al 2009;Iapichino & Lesaffre 2010). …”
mentioning
confidence: 99%